A review of hepatic fibrosis‐associated histopathology in aged cadavers. Issue 5 (21st April 2022) - Mak, Ki M.; Kee, Dustin; Cheng, Christopher P.
Abstract: This article reviews hepatic fibrosis‐associated histopathology of aged cadavers (mean age 82 years). A study of 68 livers identified steatosis in 35.5%, central vein fibrosis in 49.2%, perisinusoidal fibrosis in 63.2%, portal tract fibrosis in 47.7%, septa formation in 44.1%, bridging fibrosis in 30.8%, and cirrhosis in 4.4% of the samples as well as one hepatocellular carcinoma and six metastatic tumors. Other studies have revealed that collagens I, III, IV, V, and VI and fibronectin constitute the matrices of fibrous central veins, perisinusoidal space, portal tracts, and septa. Elastin is rich in portal tracts and fibrous septa but absent from the perisinusoidal space. Hepatic stellate cells are ubiquitous in the liver parenchyma while myofibroblasts localize in fibrotic foci. Factor VIII‐related antigen expression signals sinusoidal to systemic vascular endothelium transformation while collagen IV and laminin codistribution indicates formation of perisinusoidal membranes. Their coincidence reflects focalized capillarization of sinusoids in the aged liver. In response to fibrogenesis, hepatic progenitor cells residing in the canal of Hering in the periportal parenchyma undergo expansion and migration deep into the lobule. Concomitantly, intermediate hepatocyte‐like cells increase in advanced fibrosis stages, which is possibly related to hepatic regeneration. Metabolic zonation of glutamine synthetase expands from the perivenous to non‐perivenous parenchyma in fibrosis progression but its expression is lost in cirrhosis, while cytochrome P‐4502E1 expression is maintained in centrilobular and midlobular zones in fibrosis progression and expressed in cirrhosis. Hence, cadaveric livers provide a platform for further investigation of hepatic histopathologies associated with the aging liver.